Quantitative differences between complement factor-B phenotypes. - Mortensen, J P (1981)
In a study of 365 unrelated blood donors the structural polymorphism was determined by high-voltage electrophoresis followed by immunofixation with monospecific anti-Bf serum as described by Alper, Boenish & Watson (1972), and serum levels were measured by rocket-immunoelectrophoresis as described by Sjöholm (1975). We found that the mean level of Factor B in relation to structural phenotypes varies significantly in the order BfF greater than BfFS greater than BfS, though great variation was observed within types. A similar difference was also found with a functional assay of Factor B in agarose plates, although this method is less accurate. Concerning the biological functions, such as opsonization and bacteriolysis, it might be that individuals with the BfF allele are more able to withstand infectious agents than BfS subjects. The Bf polymorphism may therefore be transient, the BfF allele being in a process of replacing BfS by natural selection.